2005
DOI: 10.1124/jpet.104.082073
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine 1A Receptors in the Paraventricular Nucleus of the Hypothalamus Mediate Oxytocin and Adrenocorticotropin Hormone Release and Some Behavioral Components of the Serotonin Syndrome

Abstract: Neuroendocrine responses to administration of serotonin releasing agents or 5-hydroxytryptamine (5-HT) 1A receptor agonists have been used as an index of serotonin receptor function in patients with depression and other mood disorders. However, the receptor population that mediates these responses has not been clearly identified. We tested the hypothesis that 5-HT1A receptors in the paraventricular nucleus of the hypothalamus (PVN) mediate the release of adrenocorticotropin hormone (ACTH) and oxytocin after ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 41 publications
(44 reference statements)
1
37
0
Order By: Relevance
“…Although the 5-HT 1A receptors are relatively few in these regions, recent data confirm that these receptors are implicated in the regulation of various physiological processes. It was notably reported that a subpopulation of 5-HT 1A receptors in the hypothalamus could play a regulatory role in neuroendocrine secretion (Osei-Owusu et al, 2005). Furthermore, electrophysiological studies have shown that selective 5-HT 1A receptor ligands modulate the activity of dopaminergic neurons in the substantia nigra (Dugast et al, 1998;Minabe et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although the 5-HT 1A receptors are relatively few in these regions, recent data confirm that these receptors are implicated in the regulation of various physiological processes. It was notably reported that a subpopulation of 5-HT 1A receptors in the hypothalamus could play a regulatory role in neuroendocrine secretion (Osei-Owusu et al, 2005). Furthermore, electrophysiological studies have shown that selective 5-HT 1A receptor ligands modulate the activity of dopaminergic neurons in the substantia nigra (Dugast et al, 1998;Minabe et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroanatomical studies also suggest an action of 5-HT through synaptic contacts between serotoninergic terminals and CRH-containing cells in the PVN (Liposits et al, 1987). Indeed, immunohistochemical investigations demonstrated the presence of 5-HT 1A receptors on PVN neurons, and microinjection of 8-OH-DPAT into this hypothalamic nucleus was shown to trigger ACTH secretion through local 5-HT 1A receptor activation (Zhang et al, 2004;Osei-Owusu et al, 2005). In contrast, somatodendritic 5-HT 1A autoreceptors are clearly not involved in the effects of 8-OH-DPAT as 5,7-dihydroxytryptamine lesions of the serotoninergic neurons, which eliminate such receptors, do not prevent ACTH release evoked by this agonist (Van de Kar et al, 1998).…”
Section: Reciprocal Interactions Between the 5-ht System And The Hpa mentioning
confidence: 94%
“…First, MDMA may alter the sensitivity of 5-HT 1A receptors in some areas of the brain and spinal cord (i.e., those areas responsible for 8-OH-DPAT elicitation of the serotonin syndrome) but not others (i.e., areas involved in 8-OH-DPAT-induced hypothermia). Investigators have traditionally believed that the serotonin syndrome is triggered at the level of the spinal cord or brainstem (Sternbach, 1991); however, recent results of Osei-Owusu et al (2005) suggest that at least some components of this syndrome, specifically hind limb abduction and low body posture, are mediated by 5-HT 1A receptors in the paraventricular nucleus of the hypothalamus. The location of the receptors involved in the hypothermic response to 8-OH-DPAT is controversial, with some investigators favoring a presynaptic localization (i.e., in the raphe nuclei) and others favoring a postsynaptic localization, possibly in the hypothalamus (see references cited in Aguirre et al, 1998).…”
Section: Discussionmentioning
confidence: 99%